The Effect of Business Continuity Management Factors on Organizational Performance: A Conceptual Framework - Zahari Abu Bakar; Noorulsadiqin Azbiya Yaacob; Zulkifli Mohamed Udin (International Journal of Economics and Financial Issues, 2015)
This paper reviews the role played by business continuity management (BCM) factors in enhancing the organizational performance. The constructs of this paper are based on a comprehensive review of recent literature on BCM critical success factors, BCM standards and organizational performance. In this study, the organizational performance covers two specific areas of organizational results such as financial performance and non-financial performance. Financial performance which may encompass of revenue, profitability, cost saving, return on investment and other financial measures while the non-financial performance may includes effectiveness, efficiency, quality, quality of work life, innovation and productivity. A detailed literature review revealed the importance of effective BCM implementation in ensuring an organization’s survivability and competitiveness. Therefore, the demand to protect the continuity of critical business services in the event of an unforeseen disaster or disruption has become more critical than ever. In Malaysia, among the widely adopted BCM related standards by both the private and public sectors are ISO 22301 and ISO 27001. These certified organizations are selected as the population of the study as they are deemed to possess considerably higher sense of commitment towards embracing BCM best practices to enhance their business resiliency. The international standard certification may also indicate the maturity of the organizations in practicing BCM. Previous study has proven that organizations with matured BCM processes had indicated substantial performance improvements. This paper also highlights the challenges encountered by the BCM professionals in developing and maintaining the BCM infrastructure and activities, which necessitate the support from the senior management. Among the challenges that may cause failure in BCM implementation are lack of financial support and the deployment of BCM initiatives on enterprise wide basis. In summary, this paper is expected to propose the conceptual framework for future researchers to investigate and provide the empirical evidence on the relationship that exist between the BCM factors and organizational performance.